Application and Clinical Effectiveness of Antibiotic-Loaded Bone Cement to Promote Soft Tissue Granulation in the Treatment of Neuropathic Diabetic Foot Ulcers Complicated by Osteomyelitis: A Randomized Controlled Trial - Regis Ernest Mendame Ehya; Hao Zhang; Baiwen Qi; Aixi Yu (Journal of Diabetes Research)
This study explored the clinical effectiveness of antibiotic-loaded bone cement on primary treatment of diabetic foot infection. This is a randomized controlled study, including thirty-six patients with diabetic foot ulcer complicated by osteomyelitis who had undergone treatment between May 2018 and December 2019. Patients were randomly divided into control group (group A) and study group (group B). Patients in the intervention group received antibiotic-loaded bone cement repair as primary treatment, while patients in the control group received conventional vacuum sealing draining treatment. Clinical endpoints were assessed and compared between the two groups, including wound healing time, wound bacterial conversion, NRS pain score, number of wound dressing changes, and average hospitalization time. All patients were followed up for a period of 12 months after discharge. Results show that compared with the control group, patients in the study group had significant difference in the number of patients for baseline pathogens eradication, short NRS pain score, hospital length of stay and cost, wound surface reduction, healing time, low rate of complications, and infection recurrence. Based on the findings, we conclude that antibiotic-loaded bone cement can be used for treatment of wound in patient with diabetic foot infection. It can help to control wound infections, shorten hospital length of stay, reduce medical cost, and relieve both doctors’ and patients’ burden. The application of antibiotic-loaded bone cement is suitable for diabetic wound with soft tissue infection or osteomyelitis.